Cerebral folate deficiency: Analytical tests and differential diagnosis. Issue 4 (2nd May 2019) - Pope, Simon; Artuch, Rafael; Heales, Simon; Rahman, Shamima
Abstract: Cerebral folate deficiency is typically defined as a deficiency of the major folate species 5‐methyltetrahydrofolate in the cerebrospinal fluid (CSF) in the presence of normal peripheral total folate levels. However, it should be noted that cerebral folate deficiency is also often used to describe conditions where CSF 5‐MTHF is low, in the presence of low or undefined peripheral folate levels. Known defects of folate transport are deficiency of the proton coupled folate transporter, associated with systemic as well as cerebral folate deficiency, and deficiency of the folate receptor alpha, leading to an isolated cerebral folate deficiency associated with intractable seizures, developmental delay and/or regression, progressive ataxia and choreoathetoid movement disorders. Inborn errors of folate metabolism include deficiencies of the enzymes methylenetetrahydrofolate reductase, dihydrofolate reductase and 5, 10‐methenyltetrahydrofolate synthetase. Cerebral folate deficiency is potentially a treatable condition and so prompt recognition of these inborn errors and initiation of appropriate therapy is of paramount importance. Secondary cerebral folate deficiency may be observed in other inherited metabolic diseases, including disorders of the mitochondrial oxidative phosphorylation system, serine deficiency, and pyridoxine dependent epilepsy. Other secondary causes of cerebral folate deficiency include the effects of drugs, immune response activation, toxic insults and oxidative stress. This review describes the absorption, transport and metabolism of folate within the body; analytical methods to measure folate species in blood, plasma and CSF; inherited and acquired causes of cerebral folate deficiency; and possible treatment options in those patients found to have cerebral folate deficiency.